A Study on Phrases Used in Writing Thesis Abstracts - Dedi Saputra; Usuludin Usuludin; Hajriana Arfah; Siti Maysuroh (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
This study aimed to identify and analyze the types of phrases used in thesis abstracts written by students of the English Education Study Program. Phrase usage in academic writing, especially in thesis abstracts, plays an important role in presenting research information clearly, concisely, and effectively. This study focused on five types of phrases, namely noun phrases, verb phrases, adjective phrases, prepositional phrases, and adverbial phrases. The study employed a descriptive qualitative design using content analysis. The data were taken from five thesis abstracts written by students of the English Education Study Program and were classified and analyzed based on phrase categories to determine their frequency and distribution. The findings revealed a total of 463 phrases, consisting of 186 noun phrases, 85 verb phrases, 54 adjective phrases, 97 prepositional phrases, and 41 adverbial phrases. Noun phrases were the most dominant type, indicating their important role in presenting key research elements such as topics, objectives, participants, methods, and findings. The dominance of noun phrases reflects the characteristics of academic writing, which emphasize clarity and conciseness.